Caveolin-1 in Cell Migration and Metastasis - Nunez-Wehinger, S.; Ortiz, R.J.; Diaz, N.; Diaz, J.; Lobos-Gonzalez, L.; Quest, A.F.G. (Current Molecular Medicine, 2014)
Caveolin-1 is a member of the caveolin family that has been ascribed a dual role in cancer. In early stages of disease the protein functions predominantly as a tumor suppressor, whereas at later stages, caveolin-1 expression is associated with tumor progression and metastasis. Here, some mechanisms associated with caveolin-1-dependent tumor suppression will be briefly discussed before focusing on the role of this protein and particularly phosphorylation of tyrosine-14 in promoting cell migration, invasion and metastasis. Models are provided summarizing possible explanations for these dramatic changes in function, as well as mechanisms by which this may be achieved.
Keywords: migration